Plan estratégico para mejorar el servicio al cliente en la Cooperativa de Ahorro y Crédito Juan Pio de Mora. Ricaurte – Los Ríos - Arreaga Moran, María Katrina (2018)
The administrative management is fundamental in public and private companies since this factor depends on the welfare of society and the institution, it is considered a competitive advantage, even more so when organizations are in drastic changes or changes caused by the environment , different management models have been used in these companies since they must be adapted to the needs of each of them. The present work shows an investigation carried out in the credit union Juan Pio de Mora. Ricaurte - Los Ríos, in which its main or fundamental objective was to investigate the problem of how user care is within the institution. The research work includes a broad theoretical framework that presents proposals on the integral content of administrative management and how to provide an excellent service to the user, the research develops clear objectives that are the purpose of the work, in a cognitive and attitudinal way, they applied the data collection techniques of the participants. The outline of a proposal is presented, with this is intended to leave the bases for the credit union Juan Pio de Mora. Ricaurte - Los Ríos has a successful application of administrative management and how to improve customer service in the aforementioned organization.